2021
DOI: 10.1556/2006.2021.00022
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional family therapy reduces problematic gaming in adolescents: A randomised controlled trial

Abstract: Background and aimsSocial variables including parental and family factors may serve as risk factors for Internet Gaming Disorder (IGD) in adolescents. An IGD treatment programme should address these factors. We assessed two family therapies – multidimensional family therapy (MDFT) and family therapy as usual (FTAU) – on their impact on the prevalence of IGD and IGD symptoms.MethodsEligible for this randomised controlled trial comparing MDFT (N = 12) with FTAU (N = 30) were adolescents of 12–19 years old meetin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
2
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 35 publications
0
51
2
1
Order By: Relevance
“…They found that those with gaming disorder reported significant functional impairment across multiple domains, including academic and work performance, social functioning, and physical health (including problems related to sleep, pain, body weight, vision, and physical exercise). Psychological interventions designed to reduce gaming time and gaming disorder symptoms have demonstrated significant improvements in global measures of functional impairment 154,204 .…”
Section: Review Of the Evidencementioning
confidence: 99%
See 2 more Smart Citations
“…They found that those with gaming disorder reported significant functional impairment across multiple domains, including academic and work performance, social functioning, and physical health (including problems related to sleep, pain, body weight, vision, and physical exercise). Psychological interventions designed to reduce gaming time and gaming disorder symptoms have demonstrated significant improvements in global measures of functional impairment 154,204 .…”
Section: Review Of the Evidencementioning
confidence: 99%
“…The Kurihama Medical and Addiction Centre in Japan reported treating more than 200 patients with gaming disorder in 2019, which for many adolescent patients involved working with parents and other family members 157 . In the UK, the National Health Service (NHS)-funded specialist service for gaming disorder, positioned within the National Centre for Behavioural Addictions, received more than 50 patients between January and May in 2021 204 . Other studies have shown that individuals with gaming-related problems may also seek assistance from gambling treatment services 199 , units that specialize in the treatment of behavioural addictions 151,154 , broader treatment providers dealing with addictive disorders in general 204 , or non-specialized services 200 .…”
Section: Review Of the Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…Within these, treatment effectiveness is often defined by a significant reduction of digital media use times and addictive symptoms [6]. Moreover, only very few randomized controlled trial studies exist [29][30][31]. In general, CBT has been shown to be an effective treatment [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Marginally better treatment outcomes for CBT were found for short-term thinking scores. Nielsen et al [31] showed that multidimensional family therapy (MDFT) keeps families in treatment with more success than family therapy as usual (FTAU). Treatment was completed in all MDFT cases and 70% of FTAU cases.…”
Section: Introductionmentioning
confidence: 99%